2013
DOI: 10.1074/jbc.m113.503904
|View full text |Cite
|
Sign up to set email alerts
|

Farnesyltransferase Haplodeficiency Reduces Neuropathology and Rescues Cognitive Function in a Mouse Model of Alzheimer Disease

Abstract: Background: Protein prenylation may play an important role in Alzheimer disease. Results: Haplodeficiency in farnesyltransferase and geranylgeranyltransferase-1 attenuates neuropathology, but only reduction of farnesyltransferase rescues cognitive function in Alzheimer mice. Conclusion: Protein farnesylation and geranylgeranylation differentially affect the course of Alzheimer disease. Significance: Specific inhibition of protein farnesylation might be a potential strategy for effectively treating Alzheimer di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 48 publications
2
58
0
Order By: Relevance
“…If this is true, we would expect statins to protect cognitive decline by decreasing the amount of farnesylated or geranylgeranylated proteins. This hypothesis is consistent with studies showing that statins enhance long-term potentiation [48], and demonstrating that decreasing prenyltransferases like farnesyl transferase ameliorate cognitive decline in a mouse model of Alzheimer’s disease [49]. It will be interesting to learn whether similar results are seen with geranylgeranyl transferase inhibitors.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…If this is true, we would expect statins to protect cognitive decline by decreasing the amount of farnesylated or geranylgeranylated proteins. This hypothesis is consistent with studies showing that statins enhance long-term potentiation [48], and demonstrating that decreasing prenyltransferases like farnesyl transferase ameliorate cognitive decline in a mouse model of Alzheimer’s disease [49]. It will be interesting to learn whether similar results are seen with geranylgeranyl transferase inhibitors.…”
Section: Discussionsupporting
confidence: 85%
“…While some of the effects are related to decreased cholesterol [47], there is good evidence that the decrease in protein isoprenylation may also play an important role [46,48,49]. Our data suggest that statins increase neurite arborization, an aspect of neurite outgrowth that likely correlates with increased synaptic plasticity.…”
Section: Discussionmentioning
confidence: 60%
“…However, a recent report on heterozygous deletion of FTase and GGTase‐I showed reduced levels of amyloid beta‐protein and neuroinflammation in a mouse model of AD (Cheng et al . ) which can be interpreted as neuroprotective. The functional roles of prenylated proteins and isoprenoids may differ in normal aging as compared with AD.…”
Section: Discussionmentioning
confidence: 99%
“…In support of the hypothesis that SV-mediated inhibition of isoprenoid production and protein prenylation modulates LTP, we have demonstrated previously that supplement of FPP abolishes the enhancement of LTP by SV and that inhibition of farnesyltransferase mimics the effects of SV treatment (Mans et al 2012). Recently, we found that genetic reduction of farne-syltransferase rescues cognitive function in a mouse model of Alzheimer’s disease (Cheng et al 2013). Others have also shown that SV exerts neuroprotective effects by inhibiting activation of small GTPases (Lapchak and Han 2010; Ghosh et al 2009).…”
Section: Discussionmentioning
confidence: 99%